Association between Metabolic Score for Visceral Fat and the risk of hypertension in different ethnic groups: a prospective cohort study in Southwest China - Zhang, Fuyan; Wang, Yiying; Zhou, Jie; Yu, Lisha; Wang, Ziyun; Liu, Tao; Yu, Yangwen (Frontiers in Endocrinology, 2024)
Objective Visceral adipose tissue assessment holds significant importance in hypertension prevention. This study aimed to explore the association between the Metabolic Score for Visceral Fat (METS-VF), a new indicator based on laboratory and anthropometry measures, and hypertension risk and to further investigate the association between the METS-VF and the risk of hypertension in different ethnic groups. Methods In this study, a total of 9,280 people from 48 townships in 12 districts (counties) of Guizhou Province were selected for the survey using a multistage cluster random sampling method, and 5,127 cases were finally included in the analysis after excluding those with missing relevant data, losing visits, dying at follow-up, those who suffered from hypertension at baseline, and those whose information on the outcome of hypertension was not clear. Cox proportional hazard models were used to estimate hazard ratios (HRs) and 95% confidence intervals (95% CIs) between METS-VF and incident hypertension, and an accelerated failure time (AFT) model was applied to analyze the association between METS-VF and the onset time of hypertension. Results The total person-years (PYs) of the 5,127 subjects were 36,188.52 years, and the median follow-up time was 6.64 years. During follow-up, 1,127 patients were newly diagnosed with hypertension, and the incidence density was 31.14/1,000 PYs. After adjusting for multivariables, compared with the METS-VF first (Q1), the third (Q3) and fourth (Q4) groups of the METS-VF increased by 29.9% and 61.5%, respectively (HR = 1.299 [1.061, 1.590] and 1.615 [1.280, 2.036]). The risk of hypertension increased with higher METS-VF values (HR = 1.323 [1.167, 1.500], ptrend < 0.001). In the Han Chinese population, Q2 and Q3 increased the risk of hypertension (HR = 1.459 [1.111, 1.917], 1.999 [1.417, 2.718]), and the onset of hypertension was advanced by 0.653 (β = −0.653 (−0.930, −0.375]) years for per 1 unit increase in METS-VF. However, these associations were not found in ethnic minorities. Conclusion METS-VF was significantly positively associated with the risk of hypertension, and the association was different among ethnic groups.